The operating Condition and Development of Desirable Characteristics of Graduated Nursing amid the COVID-19 Pandemic in College of Nursing, Praboromarajchanok Institute - Tanyaratsrisakul, Amnouy (Journal of The Royal Thai Army Nurses, 2023)
The purpose of this describes research was to study the operating situations and guidelines for developing desirable characteristics of graduates nursing students during the COVID-19 pandemic among College of Nursing under the Praboromarajchanok Institute. The total sample of 72 the primarily responsible for academic development and graduate characteristics from 30 colleges was recruited using purposive sampling. Data were collected using a semi-structured interview focus on operating situations and guidelines for developing desirable characteristics of graduates nursing students. The data were analyzed using descriptive statistic and content analysis. The results showed that the operating situations and guidelines for developing desirable characteristics of graduates nursing students during the COVID-19 pandemic, the colleges adapt their teaching methods to online or combine with small group and postpone in some subjects (40.00 percent). For practicum, the colleges using simulation with small group workshops such as problem-based learning and simulation-based learning combined with hands-on training in wards, nursing homes and communities (86.67%) and online learning (40.00 %). Student development activities changed to online engagements (86.67 %), using a small group event, or limitation the number of student (83.33 %). Covid-19 epidemic lead the College of Nursing to develop the educational management model and educational technology systems. On the other hand, the College of Nursing unable to organize student development activities in some characteristic. Teachers need more time to prepare for teaching. Students sometimes lose interest in learning and lack of skill training in some subjects. The results of the study can be used to improve the activities to develop desirable characteristics of graduated nursing who are below the criteria.